A Statistical Analysis of Epoxy Polymer Reinforced with Micro Ceramic Particles - Lara Melo, Arthur Bernardes; Paiva, Luís Fernando Lucas; dos Santos, Júlio Cesar; Panzera, Túlio H.; Santos Freire, Rodrigo Teixeira (Journal of Research Updates in Polymer Science, 2016)
A significant amount of research has been focused on the use of ceramic nano/micro particles to enhance the strength and stiffness of polymeric matrices. This work evaluates the effect of Portland cement or crystalline silica (quartz) particle inclusions into epoxy polymer. Two experiments were conducted based on a full factorial design analysis. Experiment I investigated the effect of Portland cement amount (ASTM III), two types of hardeners (HY 951 and 956) and two curing times (7 and 28 days) on the compressive behaviour and density of particulate composites. Experiment II evaluated the incorporation of quartz or cement particles by mixing different mass fraction levels, considering 28 days of curing time and HY 951 hardener. The samples were prepared in a randomized manufacturing process and tested in compression. The mechanical properties were significantly affected by the type of hardener used. Both particles can enhance the compressive strength and stiffness of the composites.